Les défis épistémologique, théorique et méthodologique d’une stratégie de communication engageante - Thomas Maxwell (Communication)
This paper discusses the epistemological, theoretical, and methodological challenges of implementing an experimental communication procedure—engagement communication—to shape organizational behaviours. Attempts to cultivate engagement in a group of midlevel executives on the issue of integrity (one of the cardinal values asserted by the organization) have shown that engagement efforts are inseparable from their context, how engagement is portrayed in the workplace, and the authority that institutionalizes it. This is illustrated by intervention research conducted in a Québec government organization with more than 20,000 employees